Pengaruh Literasi Keuangan dan Gaya Hidup Terhadap Perilaku Menabung dengan Pengendalian Diri sebagai Variabel Intervening di Kalangan Mahasiswa - Siti Khoiriyah; Heri Prabowo; Ika Indriasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the effect of financial literacy and lifestyle on saving behavior with self-control as an intervening variable among undergraduate students of the Faculty of Economics and Business at PGRI University Semarang. This research employs a quantitative approach with data collection methods using surveys conducted through questionnaires. The population of this study consists of 1,464 undergraduate students from the Faculty of Economics and Business cohorts 2020-2023. The sampling technique used is purposive sampling, involving 314 respondents from the Management Study Program and the Digital Business Study Program. Data analysis was performed using SEM with the assistance of SmartPLS software. The results of hypothesis testing indicate that financial literacy and lifestyle have a positive and significant effect on saving behavior. Additionally, self-control serves as a mediator in the relationship between financial literacy and lifestyle on saving behavior. Keywords: , , ,